THE OUTCOME OF 810 NM SURGICAL DIODE LASER IN THE MANAGEMENT OF ORAL SOFT TISSUE LESIONS (Iraqi Journal of Medical Sciences, 2016)
Background:Surgical diode lasers have been used in oral surgical procedures with beneficial effects as compared to the conventional techniques.Objective:To evaluate the efficacy and safety of 810 nm surgical diode laser in the field of oral and maxillofacial surgery.Methods: Forty patients who had different oral lesions were attending consultation clinic of the Maxillofacial Surgery Department in the Al-Kadhimyia Teaching Hospital. The patients have been treated by 810 nm diode laser. The power of the diode laser was 2-5 Watts in continuous mode. Excisional biopsies were sent for histopathological examination. Intraoperative and postoperative clinical examinations were done.Results:The clinical observations revealed no bleeding intraoperatively and postoperatively, no infection and minimal swelling was seen postoperatively.Conclusion:The benefits of 810 nm diode laser application in oral and maxillofacial surgery have been justified based on its efficacy and safety. There is a good acceptance for this new modality of treatment by the patients.Keywords:Surgical diode laser, soft tissue lesion, oral surgery
Keywords: Surgical diode laser; soft tissue lesion; oral surgery